Heat Shock Protein 90 as a Prognostic Marker and Therapeutic Target for Adrenocortical Carcinoma - Siebert, Claudia; Ciato, Denis; Murakami, Masanori; Frei-Stuber, Ludwig; Perez-Rivas, Luis Gustavo; Monteserin-Garcia, José Luis; Nölting, Svenja; Maurer, Julian; Feuchtinger, Annette; Walch, Axel K.; Haak, Harm R.; Bertherat, Jérôme; et al. (Frontiers in Endocrinology, 2019)
Background: Adrenocortical carcinoma (ACC) is a rare tumor entity with restricted therapeutic opportunities. HSP90 (Heat Shock Protein 90) chaperone activity is fundamental for cell survival and contributes to different oncogenic signaling pathways. Indeed, agents targeting HSP90 function have shown therapeutic efficacy in several cancer types. We have examined the expression of HSP90 in different adrenal tumors and evaluated the use of HSP90 inhibitors in vitro as possible therapy for ACC. Methods: Immunohistochemical expression of HSP90 isoforms was investigated in different adrenocortical tumors and associated with clinical features. Additionally, a panel of N-terminal (17-allylamino-17-demethoxygeldanamycin (17-AAG), luminespib and ganetespib) and C-terminal (novobiocin and silibinin) HSP90 inhibitors were tested on various ACC cell lines. Results: Within adrenocortical tumors, ACC samples exhibited the highest expression of HSP90β. Within a cohort of ACC patients, HSP90β expression levels were inversely correlated with recurrence-free and overall survival. In functional assays, among five different compounds tested luminespib and ganetespib induced a significant decrease in cell viability in single as well as in combined treatments with compounds of the clinically used EDP-M scheme (etoposide, doxorubicin, cisplatin, mitotane). Inhibition of cell viability correlated furthermore with a decrease in proliferation, in cell migration and an increase in apoptosis. Moreover, analysis of cancer pathways indicated a modulation of the ERK1/2 - and AKT - pathways by luminespib and ganetespib treatment. Conclusions: Our findings emphasize HSP90 as a marker with prognostic impact and promising target with N-terminal HSP90 inhibitors as drugs with potential therapeutic efficacy towards ACC.